(untitled) (Journal of Student Affairs in Africa, 2022)
This qualitative descriptive study explored the effects of the COVID-19 pandemic and the subsequent lockdown on the emotional and social well-being of students enrolled at the Durban University of Technology, South Africa. A sample of students was selected across all levels of study (first, second and third years and postgraduates), using convenience sampling. Data saturation was reached after interviewing the fifteenth participant on Microsoft Teams. The interview schedule included details on understanding how the pandemic and the ensuing lockdown affected students’ emotional and social well-being. Interviews were recorded, transcribed and subjected to content and thematic analyses. Four broad themes emerged, viz., fears associated with coronavirus and its transmission; the lockdown experience; personal anxiety and mental health; as well as financial distress. Our study highlights the potential risks associated with the emotional and mental health status of our cohort in the advent of the COVID-19 lockdowns that characterised the immediate responses of the South African Government and institutions of higher learning to the pandemic outbreak. These data may assist our understanding of the possible adverse effects on emotional and social well-being amongst a university population. These are important factors for higher education institutions to consider in order to provide better mental health support to students.